DESIGNING AN INSTRUMENT TO EVALUATE ONLINE INFORMATION SEARCHING STRATEGIES AMONG HIGHER EDUCATION STUDENTS - Anitha. G; Rajeshkumar. M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study focuses on designing a research instrument to evaluate the online information searching strategies of higher education students. The concept of information searching is analyzed across three key dimensions: Cognitive, Search Regulation, and Metacognitive processes. Leveraging insights from experts, literature reviews, and online resources, a tool comprising 36 initial statements was developed, later refined to 26 statistically validated items based on rigorous item analysis. The tool was validated using statistical methods, including t-tests, Kolmogorov-Smirnov tests, and Cronbach's Alpha, ensuring reliability and content validity. The finalized instrument highlights the interconnectedness of the identified dimensions, providing comprehensive insights into students' online information searching behaviors. It further emphasizes the significance of integrating these dimensions to improve information-seeking systems and practices, addressing gaps in the Indian educational context.